The efficacy of using the New Zealand Child and Youth Profile in planning for children with autism spectrum disorder transitioning to school : stakeholder perspectives : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Psychology at Massey University, Albany, New Zealand - de Graaf, Shelley R. (Massey University, 2019)
This research explores use of the New Zealand Child and Youth Profile (NZCYP), an in-depth information gathering and assessment tool designed specifically for New Zealand educational contexts. The research centres on educational planning for children with Autism Spectrum Disorder (ASD) transitioning to school. Research shows that while it is essential to have successful educational transitions, particularly for children with additional needs, the processes involved in planning do not always meet best practice standards. This study takes a phenomenological approach to exploring participants’ perceptions regarding the efficacy of using the NZCYP in planning for children with ASD transitioning to school. This is answered by considering two key aspects: how stakeholders perceive the functionality of the NZCYP in planning for children with ASD transitioning to school, and how stakeholders perceive the impact that using the NZCYP has on planning for children with ASD transitioning to school. The stakeholders (parents and teachers) of two children with ASD approaching school age trialled the use of the NZCYP and were then interviewed individually. The findings of this research indicate that the majority of participants did find that the NZCYP helped to facilitate the planning for transition to school of a child with ASD. Participants noted both an improvement in their understanding of the child, and a higher standard of collaboration and communication between stakeholders. It is hoped this study will inform educational practitioners and parents about the suitability and benefits of using the NZCYP in educational planning, particularly for children with ASD.
Keywords: New Zealand Child and Youth Profile; Autistic children; Education (Early childhood); New Zealand; Readiness for school; Parents of autistic children; Teachers of children with disabilities; Attitudes; 520102 Educational psychology